Analisis Permasalahan Ergonomi pada Area Kerja Bagian Produksi dan Permesinan di PT X Karawang dengan Menggunakan Metode Ergonomic Checkpoint - Azizah Dian Ardhani; Dene Herwanto; Oktari Rabiatussyifa (Peneliti.net, 2022)
In the industrial world, ergonomics is an important aspect that needs to be implemented. In view of work accidents often occur in a company. Ergonomics aspect is useful to minimize the occurrence of accidents due to work. PT X Karawang is a company engaged in fabrication and machining. The rate of work accidents in the company is quite high. Therefore, this study aims to identify whether the application of ergonomic aspects in the production and machining work area at PT X Karawang has been carried out optimally or not, due to the high level of work accidents that occur in the company. This research was conducted using the ILO (International Labor Organization) Ergonomic Checkpoint method by assessing 132 questions regarding the sub-aspects of material storage, suitability of tool sizes, production machine safety, lighting in the work area, hazards in the work environment, and others by ticking the criteria